Extreme weather - Phelan, Glen.; National Geographic Society (U.S.) (Washington, D.C. : National Geographic Society, 2004)
Discusses extreme weather and the latest projects to improve storm prediction. Describes some of the health, economic, and environmental effects of extreme weather. Explains how thunderstorms, tornadoes, and hurricanes form, and what safety measures to take during storms. Explores the latest technology that scientists use to learn about and predict storms.
Introduction: Twister! -- Stormy weather: raging forces -- Picture this: mapping the weather -- Storm hazards and safety: nature's fury -- Predicting storms: high-tech detection -- Thinking like a scientist: interpreting data -- Hands-on science: fun with air pressure -- Science notebook -- Glossary.
Includes bibliographical references (p. 30) and index.
Keywords: Hurricanes -- Juvenile literature; Storms -- Juvenile literature; Tornadoes -- Juvenile literature; Weather forecasting -- Juvenile literature; Weather -- Juvenile literature; Hurricanes; Storms; Tornadoes; Weather forecasting; Weather